Dampak Penggunaan Handphone Terhadap Perkembangan Sosial Emosional AUD - Najwa Rahmi; Khadijah Khadijah; Yola Adela Sindy; Rama Yuspika (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
He increasing development of technology and information means that everyone can never leave the hands of this Smartphone. Because, this gadget is very useful as a means or medium for exchanging information. Apart from just exchanging information, smartphones are used as a medium for seeking knowledge. However, many young children abuse the use of smartphones without parental supervision, which ultimately has negative impacts, one of which can endanger children's motor skills and endanger children's activities and lives. This research aims to find out how mobile phones influence the social emotional development of early childhood. In this research the author also uses qualitative methods with a literature approach. The results of the research show that the influence of these gadgets is very influential on children's emotional development because this includes mental disturbances, emotional instability. So, children's use of smartphones should be accompanied by strict supervision by parents.